The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1023/b:ajcp.0000004746.31861.e7
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond the Individual: Examining the Effects of Domestic Violence Policies on Social Norms

Abstract: To be effective, criminal justice policies should affect the underlying social norms for which the policies were enacted. This study sought to determine whether public perceptionsof criminal justice policies on domestic violence affected social norms. Two waves of data were collected via a telephone survey where a random probability sample of 973 residents was drawn from 4 communities. A structural equation model was tested and confirmed. Results provided strong support for the hypothesis that perceptions of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…In summary, a public education effort aiming to reach zero tolerance towards DVAW needs to transmit the clear message that DVAW is wrong, no matter what the reason is, and must not be accepted under any circumstances. 49 Reduction of DVAW rates are thought to be related to changing the cultural norms that approve violence. 18 19 25 However, as our analysis showed, there are still widespread attitudes in the EU such as victim blaming that condone DVAW, contributing to a climate of social tolerance.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…In summary, a public education effort aiming to reach zero tolerance towards DVAW needs to transmit the clear message that DVAW is wrong, no matter what the reason is, and must not be accepted under any circumstances. 49 Reduction of DVAW rates are thought to be related to changing the cultural norms that approve violence. 18 19 25 However, as our analysis showed, there are still widespread attitudes in the EU such as victim blaming that condone DVAW, contributing to a climate of social tolerance.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Views of spousal hitting, however, then underwent a re-evaluation in the light of both the testimony of victims, a new ideology emanating from the women's movement and considerable empirical research (Salazar, Baker, Price, & Carlin, 2003;Straus, 1995;Straus, Kaufman Kantor, & Moore, 1997). One of the main differences in the case of children in comparison to spouses is that testimony from victims is not nearly as publicly available or credible, which makes the role of research even more important.…”
Section: Implications For Practitionersmentioning
confidence: 99%
“…Our work and that of others has shown that women who are abused are most likely to turn to those who are nearest to them, in geographic and psychological proximity. [8][9][10][11] Therefore, while social norms toward IPV in general have been shown to dramatically affect the rates and tolerance of IPV in communities, [12][13][14][15][16][17][18][19][20] investigations into the perceived availability of resources and response to IPV are in need of assessment. Low-income women living in an urban area represent a noteworthy sample to assess because many may lack financial resources to leave and relocate to a different environmental context, but have the availability of neighbors in relative close proximity to potentially depend upon for assistance.…”
Section: Introductionmentioning
confidence: 99%
“…8,11,15 These norms can have significant influence on how support for one who has experienced IPV is perceived by the victim, the perpetrator, and the community. [16][17][18]24 A woman's decision to remain in a violent relationship or to flee is complex, controversial, and centers on the woman's perception of the availability of resources. 25 The dynamics of abusive relationships are often misunderstood, and can lead to victim blaming when women choose to stay with their abusers.…”
Section: Introductionmentioning
confidence: 99%